Artificial intelligence in oral medicine and oral radiology - Isha P Kale; Amit A Mhapuskar; Muskan Jhawar; Darshan R Prasad Hiremutt (Wolters Kluwer Medknow Publications, 2023)
Background: The field of artificial intelligence (AI) has computational models that can learn from the data handed to them. The branch of oral medicine and radiology deals with diagnosis, treatment planning, and radiographic interpretation. The application of AI in this field has given a new perspective to this branch of dentistry. Aim: The current review article was carried out to discuss the applications of AI in the branches of oral medicine and radiology. Methods: Electronic databases such as PubMed, Google Scholar, Web of Science, and Scopus were searched with the keywords "artificial intelligence," "oral medicine," "oral radiology," "recent advancements," and "dental applications." Results: Forty articles were studied and analyzed critically for this review. Conclusions: The implementation of AI in oral medicine and radiology has helped revolutionize the standard, worth, and extent of interpretation thus elevating radiology's contribution to diagnosis and the general health of the population at large.